Proteasome inhibition and its therapeutic potential in multiple myeloma - Ajai Chari (Dove Medical Press, 2010)
Ajai Chari1, Amitabha Mazumder2, Sundar Jagannath11Mount Sinai School of Medicine, New York, NY, USA; 2New York University School of Medicine, New York, NY, USAAbstract: Due to an unmet clinical need for treatment, the first in class proteasome inhibitor, bortezomib, moved from drug discovery to FDA approval in multiple myeloma in an unprecedented eight years. In the wake of this rapid approval arose a large number of questions about its mechanism of action and toxicity as well as its ultimate role in the treatment of this disease. In this article, we briefly review the preclinical and clinical development of the drug as the underpinning for a systematic review of the large number of clinical trials that are beginning to shed some light on the full therapeutic potential of bortezomib in myeloma. We conclude with our current understanding of the mechanism of action of this agent and a discussion of the novel proteasome inhibitors under development, as it will be progress in these areas that will ultimately determine the true potential of proteasome inhibition in myeloma.Keywords: bortezomib, multiple myeloma